Ask the experts: Injecting hope into brain cancer treatment: is immunotherapy the way forward?. (January 2014) - Dietrich, Pierre-Yves
Pierre-Yves Dietrich is a Full Professor of Medicine at the University of Geneva (Geneva, Switzerland) and Director of the Centre of Oncology in the Geneva University Hospital (Geneva, Switzerland). Since the early 1990s, his clinical and research activities have focused on the interplay between cancer and the immune system. He founded the Laboratory of Tumor Immunology in the Geneva University Hospital in 1994 and investigated mouse brain tumor models as well as human gliomas to firmly establish the existence of antiglioma immunity, a concept that was being debated at the time owing to the special immune status of the brain. Dietrich then embarked upon translating these conceptual advances into glioma immunotherapy. This challenge involved identifying novel targets on the surface of glioma cells in vivo, an essential step in designing an efficacious vaccine. Thanks to a fruitful collaboration with Immatics (Tübingen, Germany), a spin-off from the University of Tübingen (Germany), this work led to the identification of ten novel glioma-associated antigens with high expression on tumor cells and faint or absent expression on normal tissues, an indispensable feature to avoid autoimmunity. This crucial advance allowed the initiation of clinical trials of peptide vaccination in patients with gliomas as well as the development of T-cell therapy.